Pengaruh Struktur Aktiva, Current Ratio, Ukuran Perusahaan, dan Pertumbuhan Penjualan terhadap Struktur Modal: (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Peralatan Rumah Tangga di Bursa Efek Indonesia Peridoe 2019-2023) - Chyntia Chantikaruby; Retno Fuji Oktaviani (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to determine the Influence of Asset Structure, Current Ratio, Firm Size and Sales Growth Relative to the Company's Capital Structure. The research population is a household appliance sub-sector manufacturing company listed on the Indonesia Stock Exchange. Sample selection using Purposive Sampling. The research period is 2019-2023. The data analysis technique used is multiple linear regression processed with IBM programs Statistical Package for Social Science (SPSS) Version 26. The results of the study show that the Asset Structure and Current Ratio have a negative and significant effect on the Capital Structure. Company Size and Sales Growth have no effect on the Capital Structure.